Assessing the Synergy of Spring Strip Tillage and Straw Mulching to Mitigate Soil Degradation and Enhance Productivity in Black Soils - Zhihong Yang; Lanfang Bai; Tianhao Wang; Zhipeng Cheng; Zhen Wang; Yongqiang Wang; Fugui Wang; Fang Luo; Zhigang Wang (Agronomy, 2025)
To address the critical challenges of wind erosion mitigation and sustainable soil management in the fragile agroecosystem of the black soil region in the foothills of the Daxing’anling Mountains, this study evaluated five tillage practices—conventional ridge tillage (CP), no tillage with straw removal (NT), no tillage with straw mulching (R+NT), autumn strip tillage with straw mulching (R+STA), and spring strip tillage with straw mulching (R+STS)—across two landforms: gently sloped uplands and flat depressions. The results demonstrated that R+STS achieved superior performance across both landscapes, exhibiting a 42.99% reduction in the wind erosion rate, a 48.88% decrease in soil sediment discharge, and a 52.26% reduction in the soil creep amount compared to CP. These improvements were mechanistically linked to the enhanced surface microtopography (aerodynamic roughness increased by 1.8–2.3 fold) and optimized straw coverage (68–72%). R+STS also enhanced the topsoil fertility, increasing the total nitrogen (TN), soil organic carbon (SOC), alkaline nitrogen (AN), available phosphorus (AP), and rapidly available potassium (AK) by 22.07%, 12.94%, 14.92%, 32.94%, and 9.52%, respectively. Furthermore, it improved maize emergence and its yield by 10.04% and 9.99% compared to R+NT. Mantel tests and SEM revealed strong negative correlations between erosion and nutrients, identifying nitrogen availability as the key yield driver. R+STS offers a sustainable strategy for erosion control and productivity improvement in the black soil region.